Juniperus pingii var. wilsonii acidic polysaccharide: Extraction, characterization and anticomplement activity. (1st March 2020) - Xia, Long; Deji,; Zhu, Mengxia; Chen, Daofeng; Lu, Yan
Graphical abstract: Highlights: A homogeneous polysaccharide XB-PS3 was isolated from Juniperus pingii var. wilsonii . XB-PS3 was proposed to be an acidic polysaccharide with good anticomplement activity. The uronic acids and branch structure play important roles in XB-PS3's activity. Abstract: A water-soluble acidic polysaccharide, XB-PS3, was isolated from the twigs of Juniperus pingii var. Wilsonii with a molecular weight of 86.04 kDa. By means of monosaccharide composition analysis, methylation, 2D NMR spectroscopy and UPLC-MS analysis, we concluded that XB-PS3 had a backbone composed of →2, 4)-α-Man p -(1→ and →4)-α-Gal p A-(1→ (60 % esterified), with an araban branch attached to O-2 of →2, 4)-α-Man p -(1→. The possible repeating units were further validated by oligosaccharide analysis and partial acid hydrolysis. XB-PS3 exhibited potent anticomplement activity with CH50 value of 117.23 ± 18.74 μg/mL and interacted with C3, C4, C5 and C9 in the complement activation cascade. However, the anticomplement activity was significantly weakened when the galacturonic acids were reduced (CH50 : 268.55 ± 16.82 μg/mL) or the branches were removed by partial hydrolysis (CH50 : 197.76 ± 21.81 μg/mL), indicating the important role of uronic acids and branch structure in the polysaccharide's anticomplement activity.